A feasibility study for CO2 recycle assistance with coke oven gas to synthetic natural gas. (1st May 2017) - Yi, Qun; Wu, Guo-sheng; Gong, Min-hui; Huang, Yi; Feng, Jie; Hao, Yan-hong; Li, Wen-ying
Graphical abstract: Highlights: CO2 recycle assistance with COG to SNG is proposed. SNG production is increased by 14% through CO2 recycle. CO2 recycle scheme helps to convert 20% CO2 and capture 80% CO2 . CO2 recycle simplified carbon supplementary with resulting of 6–7% energy saving. Abstract: Based on the industrial technology from coke oven gas to synthetic natural gas, a process of CO2 recycle assistance with coke oven gas to synthetic natural gas is proposed, simulated, and optimized. The effects of key parameters on the performance of new system are investigated and the optimum parameters are determined. The coke oven gas reacts with the recycled CO2 separated from the CO2 -rich exhaust gas to produce syngas for synthetic natural gas production. This CO2 recycle can significantly improve the hydrogen utilization efficiency in coke oven gas, which does not only increases the synthetic natural gas production and thus enhancing energy efficiency, but also reduces the CO2 emission simultaneously. The results show that the energy and exergy efficiency (79.0% and 81.1%) of the new process is increased by 6.3 and 6.6 percent points, synthetic natural gas production cost and direct CO2 emission reduced by 0.05 US/m 3 and 99.9%, whereas the synthetic natural gas output increased by 20%, in comparison with the conventional coke oven gas to synthetic natural gas process. The proposed system provides a promising way for future improvements of coke oven gas to synthetic natural gas process, and can also be a guide for CO2 utilization or CO2 emission reduction in coking industry.